Rethinking: challenges and methodological dilemas in research music - Cardoso, Mário (2015)
The musical development does not present itself as a one-way process, but as a process strongly marked by a spiral approach as convergence center of different sizes, where the interrelationships and linkages contributed to the establishment of a great cohesion texture. The expression that man composes the music and the music makes up the man is the maieutic featuring and of course reflecting the influence and interrelationship between the music and the man, in fact, of all human activities, music, characterized whether by its ubiquity both for its antiquity. The changes made to the musical universe resulting from the technological development in terms of the structures that guide the World Wide Web have led to a change of the canons associated to the way of thinking, feeling and create the contemporary musician. All systems and technological structures, developed academic and industrial level, allowed the natural appearance of independence and freedom of expression of local musicians, which are associated with connectivity and global visibility of their art. All these facts, place these days that the research object of musicology can know and include, beyond the guidelines that are already in its genesis, a wide range of sociological and ideological issues. Thus, building on the existing musician profile, which relate all these elements, this communication is to discuss and contribute, through the analysis of different narratives that mark the universe of different musical scenes, to the establishment of key guiding lines for the development of the whole musicological research in these DIY communities.